Health belief model and the understanding of rational use of medicines - Putu Eka Arimbawa; I Putu Gede Adi Purwa Hita; Zainal Firdaus Wardhana (Intelektual Pustaka Media Utama, 2021)
Community perception is an experience that causes a different understanding of treatment. Differences in people's perceptions of drug safety will affect their attitudes towards rational use of medicines (RUM). Therefore, it is necessary to do an in-depth measurement of public perceptions. The purpose of this study was to determine the relationship between community perceptions through the health belief model (HBM) with the understanding of (RUM). This study used a cross-sectional design with 97 samples in Denpasar City, Bali, Indonesia. Data collection was conducted from November 2019 to January 2020 using a questionnaire and analyzed using binary logistic tests. The results showed that perceptions based on perceived susceptibility perceived severity, health motivation, perceived benefits, and self-efficacy did not provide a significant relationship with the understanding of RUM (p>0.05). Perceived barriers provide significant results on the understanding of RUM (p<0.05). Health perceptions in allergy reporting and awareness of drug use based on clinical conditions and selection of alternatives increase understanding of rational drug use. The drug-taking procedure needs to be done quickly and according to the provisions to appropriately use the medication. Therefore, health workers' role is essential in providing complete services and information about drugs in health care, especially in symptomatic drugs.